De novo Transcriptome Assembly of Chinese Kale and Global Expression Analysis of Genes Involved in Glucosinolate Metabolism in Multiple Tissues - Wu, Shuanghua; Lei, Jianjun; Chen, Guoju; Chen, Hancai; Cao, Bihao; Chen, Changming (Frontiers in Plant Science, 2017)
Chinese kale, a vegetable of the cruciferous family, is a popular crop in southern China and Southeast Asia due to its high glucosinolate content and nutritional qualities. However, there is little research on the molecular genetics and genes involved in glucosinolate metabolism and its regulation in Chinese kale. In this study, we sequenced and characterized the transcriptomes and expression profiles of genes expressed in 11 tissues of Chinese kale. A total of 216 million 150-bp clean reads were generated using RNA-sequencing technology. From the sequences, 98,180 unigenes were assembled for the whole plant, and 49,582~98,423 unigenes were assembled for each tissue. Blast analysis indicated that a total of 80,688 (82.18%) unigenes exhibited similarity to known proteins. The functional annotation and classification tools used in this study suggested that genes principally expressed in Chinese kale, were mostly involved in fundamental processes, such as cellular and molecular functions, the signal transduction and biosynthesis of secondary metabolites. The expression levels of all unigenes were analyzed in various tissues of Chinese kale. A large number of candidate genes involved in glucosinolate metabolism and its regulation were identified, and the expression patterns of these genes were analyzed. We found that most of the genes involved in glucosinolate biosynthesis were highly expressed in the root, petiole and in senescent leaves. The expression patterns of ten glucosinolate biosynthetic genes from RNA-seq were validated by quantitative RT-PCR in different tissues. These results provided an initial and global overview of Chinese kale gene functions and expression activities in different tissues.